Morphological and Histopathological Study of the Liver of Three Species of Syrian Birds (Tyto Alba, Turdus Merula, and Carduelis Spinus) - Ebrahim, Nahla; Shalfa, Maha; Hasan, Baraa (International Journal of Scientific Research in Biological Sciences, 2021)
The current research was conducted to study histopathologically and morphologically the liver of three species of Syrian birds (Tyto alba, Turdus merula, and Carduelis spinus). The results showed that the liver occupies the upper right part under the heart from the thoracic abdominal cavity. Its color ranges from pinkish red to dark red. Its weights ranged between 0419-4.453 g depending on the type studied. A thin capsule surrounds the liver cosisting of fibrous connective tissue , divides the liver into two main lobes (right and left) that differ in size and shape of the edges and the presence of the secondary lobes. The histological study of the liver showed that the barriers between the lobules are not clear in the studied species, but the beginning of these septa was clear to the blackbird. In both owls and Eurasian siskin birds, the liver tissue is chordate, while this tissue is reticulated in the blackbird, with an observation of the beginning of the chordal alignment of multifaceted cells, with spherical near-central nuclei containing one or two nuclei. The blood sinuses are abundant. The adipocytes were observed around the sinuses, as well as, the Kupffer cells were found within the lumen of the endothelial boundaries. The portal space (hepatic triad) appeared clearly within the liver tissue of the owls, but the matter differs in both Eurasian siskin and the blackbird as they have a semi-portal distance (which means divergence among each artery, vein, and bile duct).